Minimum requirements for electron–positron pair creation in the interaction of ultra-short laser pulses with thin foils - Lécz Zsolt; Andreev Alexander (2019)
Current laser technology allows the production of extremely high laser intensities and brings ever closer experimental probing of quantum electro-dynamic effects e.g. radiation reaction and electron–positron pair creation via the multiphoton Breit–Wheeler process. The exponential dependence of the latter process on laser intensity means that the process appears suddenly above some threshold, which is still not well defined in the case of laser-plasma interactions. The threshold intensity for the generation of a significant number of positrons is shown to be in the order 1022 W cm−2, when optimal target properties, as presented in this paper, are considered. With the help of a modified particle-in-cell code, the detailed angular-energy distribution of positrons is presented, which is in good agreement with our simple analytical model.
Keywords: Fizikai tudományok